2008
DOI: 10.1152/ajpcell.00092.2008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of angiotensin II receptors and extracellular matrix turnover in human retinal pigment epithelium: role of angiotensin II

Abstract: Striker GE, Praddaude F, Alcazar O, Cousins SW, MarinCastañ o ME. Regulation of angiotensin II receptors and extracellular matrix turnover in human retinal pigment epithelium: role of angiotensin II. Am J Physiol Cell Physiol 295: C1633-C1646, 2008. First published October 15, 2008 doi:10.1152/ajpcell.00092.2008.-The early stage of age-related macular degeneration (AMD) is characterized by the formation of subretinal pigment epithelium (RPE) deposits as a result of the dysregulation in the turnover of extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 75 publications
1
29
0
Order By: Relevance
“…1,18,23,26 In this regard, MMP-2 is the most abundant and important MMP enzyme synthesized by the RPE relevant to retinal disorders such as AMD, in which its activity is dysregulated. 53,54 Moreover, MMP-2 is crucial in degradation of ECM proteins in the RPE basement membrane and BrM 4,19,55, .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,18,23,26 In this regard, MMP-2 is the most abundant and important MMP enzyme synthesized by the RPE relevant to retinal disorders such as AMD, in which its activity is dysregulated. 53,54 Moreover, MMP-2 is crucial in degradation of ECM proteins in the RPE basement membrane and BrM 4,19,55, .…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] It has been recently demonstrated that Ang II induces AT1-mediated breakdown of the RPE basement membrane by increasing MMP-2 activity in RPE. 18,26 A concomitant increase in MMP-14 expression has also been demonstrated, which might account, at least in part, for the Ang II-induced increase in MMP-2 activity. 18 Another potential regulator of MMPs is basigin (BSG), also known as extracellular MMP inducer or CD147, which is a protein that induces MMP-2 and MMP-14 in various cell types.…”
mentioning
confidence: 93%
See 3 more Smart Citations